MXOy-PAN composite membrane as well as preparation method and application thereof
By introducing metal oxide modifiers into the polyacrylonitrile film and preparing the MXOy-PAN composite film by electrospinning-alkali-heat treatment method, the problems of high cost and low efficiency in the treatment of iodine-containing wastewater in the prior art are solved, and efficient and economical iodine ion removal effect is achieved.
Patent Information
- Application Number
- CN202510240826.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art has problems such as high cost, difficulty in desorption, and complex subsequent treatment when treating iodine-containing wastewater, making it difficult to effectively reduce the content of iodine ions in the water.
Polyacrylonitrile (PAN) is used as the film-forming substance, combined with metal oxides such as Ag2O, Ag2O-TiO2, CuO, Cu2O and Cu2O as modifiers, and MXOy-PAN composite film is prepared by electrospinning-base-heat treatment method to improve its porosity, specific surface area and metal ion adsorption capacity.
It achieves efficient adsorption and removal of iodine ions, with an adsorption capacity of up to 90.0 mg/g, combined with ultraviolet treatment, the total removal rate reaches more than 95%, and is simple in process and cost-effective.
Smart Images

Figure CN119838449A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of environmental protection materials, and specifically relates to an M X O y -PAN composite membrane and its preparation method and application, suitable for iodine-containing wastewater treatment. Background Art
[0002] Iodine is one of the essential trace elements for the human body. Iodine deficiency can affect brain development and cognitive function, cause thyroid dysfunction and immune system abnormalities, etc. However, excessive iodine can also cause thyroid diseases such as goiter, hypothyroidism or hyperthyroidism, and even thyroid cancer. Therefore, the World Health Organization recommends that the daily iodine intake for school-age children and adults is 120μg and 150μg respectively, and the upper limit for infants and young children is 50-100μg. However, the total iodine concentration of water sources in some areas exceeds 300μg / L. In addition, with the development of shale gas, the iodine ion concentration in nearby waters has also increased significantly.
[0003] It should also be pointed out that nuclear power plant nuclear leakage accidents, nuclear medicine, etc. also lead to an increase in the content of radioactive I-129 and I-131 in water, which greatly harms the ecological environment and human health. Therefore, it is urgent to reduce the iodine content in high-iodine waters and treat radioactive iodine-containing wastewater.
[0004] Compared with chemical precipitation, membrane electrolysis, ion exchange, biological transformation and other methods, the adsorption method has the advantage of being simple and easy to use in treating iodine-containing wastewater. The materials used involve bismuth-based and silver-based adsorbents, metal organic framework compounds, oxides, layered hydroxides, etc. However, most adsorbents have the disadvantages of high cost, difficult desorption, and complex subsequent treatment, which to a certain extent limit the promotion and application of the adsorption method. Summary of the invention
[0005] The object of the present invention is to provide a X O y -PAN composite film and its preparation method and application. X O y-PAN composite membrane uses polyacrylonitrile as the film-forming material, Ag2O, Ag2O-TiO2, CuO, and Cu2O as modifiers, and is prepared by electrospinning-alkali-heat treatment. Appropriate alkali treatment can generate a large number of carboxylate and amide groups in polyacrylonitrile. At the same time, the porosity of the electrospinning membrane after alkali treatment increases, and the adsorption sites increase. The above promotes the adsorption of metal ions by the membrane, increases the concentration of metal ions on the fiber surface, and is conducive to the reaction of metal ions with alkali to form hydroxides, and later decomposes to form metal oxides. In addition, the electrospun fiber has a large specific surface area, which is conducive to the absorption of the precursor solution of the oxide, further promotes the formation of oxides, and provides them with abundant loading sites, thereby improving the adsorption of iodine ions. Compared with commonly used bismuth-based adsorbents, it has the characteristics of large adsorption capacity, simple preparation, high cost performance, and good prospects for technology transformation. It is a high-quality new material for the treatment of iodine-containing wastewater, and provides new ideas for the construction of high-quality iodine-containing wastewater treatment materials.
[0006] The present invention is achieved through the following technical solutions. x O y -PAN composite membrane, polyacrylonitrile or TiO2 modified polyacrylonitrile is electrospun to obtain polyacrylonitrile or TiO2 modified polyacrylonitrile fiber membrane, which is then treated with an alkali solution, immersed in a metal nitrate solution for reaction, and finally heat treated to obtain a metal oxide M x O y The composite membrane is modified by a modifier, thereby obtaining a composite fiber membrane material with large specific surface area, high porosity and rich in carboxyl and amide groups.
[0007] More preferably, the metal oxide is any one of Ag2O or Ag2O-TiO2 binary metal oxide, copper oxide, and cuprous oxide.
[0008] The present invention also provides a x O y -PAN composite film preparation method, the steps are as follows:
[0009] Step 1: preparing polyacrylonitrile fiber membrane or TiO2 modified polyacrylonitrile fiber membrane;
[0010] Step 2: treating the obtained polyacrylonitrile fiber membrane or TiO2-modified polyacrylonitrile fiber membrane with an alkaline solution;
[0011] Step 3: immersing the polyacrylonitrile fiber membrane treated with an alkali solution or the TiO2-modified polyacrylonitrile fiber membrane in a metal nitrate solution for reaction;
[0012] Step 4: heat-treat the polyacrylonitrile fiber membrane or TiO2-modified polyacrylonitrile fiber membrane treated in step 3, then wash and dry to obtain M x O y-PAN composite film.
[0013] More preferably, the alkaline solution is an alkali metal hydroxide solution with a concentration of 0.5 to 3.0 mol / L, such as a NaOH solution.
[0014] More preferably, the temperature of the alkaline solution treatment is 45° C., and the reaction time is 10 to 60 minutes.
[0015] Further preferably, the metal nitrate solution is AgNO3 solution or copper nitrate solution.
[0016] More preferably, the temperature of the heat treatment in step 3 is 50-80° C. and the time is 3-10 min.
[0017] Further preferably, the preparation process of polyacrylonitrile (PAN) fiber membrane is as follows: first prepare 13.8wt% polyacrylonitrile spinning solution, then spin at a liquid supply rate of 0.5ml / h, a roller speed of 150 rpm, a slide stroke of 20cm, a spinning voltage of 13kV, and a spinning time of 180min, and obtain the polyacrylonitrile fiber membrane after drying.
[0018] Further preferably, the preparation process of the TiO2 modified polyacrylonitrile fiber membrane is to uniformly disperse a certain amount of TiO2 in an N,N-dimethylacetamide solution, and then PAN :m TiO2 =15:0.01~15:0.07 ratio of polyacrylonitrile, stirring at 65°C, degassing to obtain 13.8wt% TiO2 / PAN spinning solution; then spinning at a liquid supply rate of 0.5ml / h, a roller speed of 150 rpm, a slide stroke of 20cm, a spinning voltage of 13kV, a spinning time of 180min, and drying to obtain TiO2 modified polyacrylonitrile fiber membrane.
[0019] The present invention also provides M x O y -Application of PAN composite membrane in reducing iodine ion content in water.
[0020] The present invention is different from other granular adsorbents in that it is a membrane material with sufficient raw material sources, convenient application and recycling, and high cost performance.
[0021] Different from other silver-containing electrospinning membranes, the present invention cleverly uses the property that the polyacrylonitrile membrane body can react with alkali to generate carboxylate radicals. After preparing polyacrylonitrile fiber membrane or TiO2-modified polyacrylonitrile fiber membrane by electrospinning, an alkaline solution treatment process is implemented. This process can not only adjust the morphology and porosity of the membrane, but also generate carboxyl radicals, amides and other coordination groups. The introduction of the above groups, combined with the porosity of the electrospinning membrane, can induce the membrane to introduce more metal ions, thereby promoting the subsequent in-situ generation of metal oxides and improving the adsorption capacity of iodide ions. In addition, Ag2O, Ag2O-TiO2, CuO, and Cu2O have photocatalytic activity, so they can further catalyze and oxidize iodine ions after ultraviolet irradiation, thereby improving the removal rate of iodine ions.
[0022] Specifically, the membrane structure is adjusted from the following aspects to improve the removal rate of iodine ions:
[0023] (1) Electrospinning was used to construct the membrane body, making full use of the high specific surface area of electrospun fibers to enhance the physical adsorption of iodine ions by the membrane.
[0024] (2) Appropriate alkaline treatment increases the effective negative charge on the membrane surface and the local concentration of metal ions near the membrane surface. At the same time, it provides a large number of coordinating groups such as carboxyl and amide, which is beneficial to the adsorption of metal ions and promotes the in situ formation of metal oxides on the membrane in the later stage, thereby further improving the chemical adsorption of iodine ions by the membrane.
[0025] (3) Appropriate alkali treatment of the electrospun membrane and the appropriate introduction of nano-TiO2 into the spinning solution can further adjust the microstructure of the membrane, improve the porosity and specific surface area of the membrane, increase the metal oxide loading sites, and promote the overall adsorption of iodine ions.
[0026] (4) Based on the photocatalytic effect of Ag2O, TiO2, CuO, and Cu2O under ultraviolet light irradiation, the material is given another iodine removal mechanism, thereby improving the overall iodine ion removal rate of the membrane.
[0027] In addition, the antibacterial property of the membrane is improved, effectively extending the service life of the membrane.
[0028] The present invention adopts electrospinning-alkali-heat treatment to construct an organic-inorganic hybrid M suitable for iodine ion removal. x O y -PAN composite membrane. The composite membrane has high porosity and large specific surface area. Based on the electrostatic, chemical adsorption and photocatalytic coupling effects, the removal rate of iodine ions is as high as over 95%. The raw material source is sufficient, the cost performance is high, and it has good application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the SEM image of the product obtained in Example 1.
[0030] Figure 2 This is the XRD pattern of the product obtained in Example 1. DETAILED DESCRIPTION
[0031] The present invention is further explained in detail below.
[0032] A kind of M x O y -PAN composite membrane preparation method, the steps are as follows: polyacrylonitrile fiber membrane or TiO2 modified polyacrylonitrile fiber membrane
[0033] Step 1, electrospinning: using polyacrylonitrile (PAN) or TiO2 / PAN as raw materials, an electrospinning method is used to prepare a polyacrylonitrile fiber membrane or a TiO2-modified polyacrylonitrile fiber membrane;
[0034] Step 2, alkaline solution treatment: then placing the polyacrylonitrile fiber membrane or TiO2 modified polyacrylonitrile fiber membrane in a 0.5-3.0 mol / L NaOH solution for reaction at 45°C for 10-60 min to obtain an alkaline solution treated polyacrylonitrile fiber membrane or TiO2 modified polyacrylonitrile fiber membrane;
[0035] Step 3: Immersing: Immerse the polyacrylonitrile fiber membrane treated with alkaline solution or the TiO2-modified polyacrylonitrile fiber membrane in a 0.01 mol / L AgNO3 solution for 30 min;
[0036] Step 4, heat treatment and cleaning and drying: Take out the polyacrylonitrile fiber membrane or TiO2 modified polyacrylonitrile fiber membrane treated in step 3, put it into an oven at 50°C to 80°C for reaction for 3 to 10 minutes, take it out, clean it, and dry it to obtain an Ag2O / PAN composite membrane or an Ag2O-TiO2 / PAN composite membrane.
[0037] The present invention is based on thermoplastic polymers, metal oxide M x O y It is a modifier, which is prepared by electrospinning-alkali-heat treatment process. The membrane structure and performance can be easily adjusted by changing the electrospinning conditions, alkali treatment process, oxide addition amount, etc.
[0038] The thermoplastic polymer used in the present invention is polyacrylonitrile.
[0039] The metal oxide M used in the present invention x O y Ag2O, Ag2O-TiO2 binary metal oxide, copper oxide, cuprous oxide. It should be noted that if copper oxide, cuprous oxide and other metal oxides are used, the solution in step 3 is replaced with a corresponding soluble copper salt, such as copper nitrate.
[0040] The composite membrane disclosed in the method has a large adsorption capacity for iodine ions in water, which is higher than 90.0 mg / g, far greater than the market products. Combined with ultraviolet treatment, the total removal rate of iodine ions in water reaches more than 95%. The composite membrane has a simple preparation process, a high cost-effective product, is suitable for iodine-containing wastewater treatment, and has good application prospects.
[0041] The present invention adopts ultraviolet-visible spectrophotometry to evaluate the performance of the material in removing iodine ions in water.
[0042] (1) Adsorption process
[0043] Take 0.1g of membrane and place it in 100ml of 100mg / L I - After adsorption in the solution for 24 h, the iodide ion concentration in the solution before and after adsorption was tested, and the adsorption capacity of the membrane was calculated according to formula (1).
[0044] The adsorption capacity of the electrospun membrane for iodide ions was calculated based on the concentration difference of iodide ions before and after adsorption on the electrospun membrane.
[0045]
[0046] Among them, q e is the equilibrium adsorption capacity of iodide ions per unit mass of electrospun membrane, unit: mg / g; C0 is the initial concentration of iodide ion solution, mg / L; C e is the adsorption equilibrium concentration of iodide ion solution, mg / L; V is the volume of iodide ion solution, L; m is the amount of electrospinning membrane, g.
[0047] (2) Total iodine ion removal rate test: The sample that has reached adsorption equilibrium is illuminated under one sun intensity, and 1 ml of solution is taken every 10 minutes to test the iodine ion concentration until the iodine ion concentration no longer changes. The total iodine ion removal rate after (adsorption-illumination) treatment is calculated according to formula (2).
[0048]
[0049] Where C0 is the initial concentration of iodide ion solution, mg / L; C e ' is the final equilibrium concentration of iodide ion solution, mg / L.
[0050] Example 1
[0051] Electrospinning: 0.05g TiO2 was evenly dispersed in N,N-dimethylacetamide solution, then 15g polyacrylonitrile was added, stirred at 65℃, and degassed to obtain 13.8wt% TiO2 / PAN spinning solution. Then, the spinning was performed at a liquid supply rate of 0.5ml / h, a roller speed of 150 rpm, a slide stroke of 20cm, a spinning voltage of 13kV, and a spinning time of 180min. After drying, 05-TiO2-PAN electrospinning membrane was obtained.
[0052] Alkaline solution treatment: The 05-TiO2-PAN electrospun membrane was placed in a 2.5 mol / L NaOH solution at 45°C for 40 min;
[0053] Immersion: The 05-TiO2-PAN electrospun membrane treated with alkaline solution was immersed in 0.01 mol / L AgNO3 solution for 30 min and then taken out;
[0054] Heat treatment and cleaning and drying: The impregnated 05-TiO2-PAN electrospinning membrane was placed in an oven at 60°C for reaction for 5 minutes, taken out, cleaned, and dried to obtain product 1.
[0055] Example 2
[0056] Electrospinning: first prepare 13.8wt% PAN spinning solution, then supply solution at a rate of 0.5ml / h, roller speed at 150 rpm, slide stroke at 20cm, spinning voltage at 13kV, spinning time at 180min, and obtain PAN fiber membrane after drying.
[0057] Alkaline solution treatment: The PAN fiber membrane was placed in 2.5 mol / L NaOH solution at 45°C for 40 min;
[0058] Immersion: Immerse the PAN fiber membrane treated with alkaline solution in 0.01 mol / L AgNO3 solution for 30 min and take it out;
[0059] Heat treatment and cleaning and drying: the impregnated PAN fiber membrane was placed in an oven at 60°C for reaction for 5 minutes, taken out, cleaned, and dried to obtain product 2.
[0060] Example 3
[0061] Electrospinning: first prepare 13.8wt% PAN spinning solution, then supply solution at a rate of 0.5ml / h, roller speed at 150 rpm, slide stroke at 20cm, spinning voltage at 13kV, spinning time at 180min, and obtain PAN fiber membrane after drying.
[0062] Alkaline solution treatment: The PAN fiber membrane was placed in 3 mol / L NaOH solution at 45°C for 10 min;
[0063] Immersion: Immerse the PAN fiber membrane treated with alkaline solution in 0.01 mol / L AgNO3 solution for 30 min and take it out;
[0064] Heat treatment, cleaning and drying: The impregnated PAN fiber membrane was placed in an oven at 60°C for reaction for 5 minutes, taken out, cleaned, and dried to obtain product 3.
[0065] Example 4
[0066] Electrospinning: 0.01g TiO2 was evenly dispersed in N,N-dimethylacetamide solution, then 15g polyacrylonitrile was added, stirred at 65°C, and TiO2 / 13.8wt% PAN spinning solution was obtained after degassing. Then, the spinning was carried out at a liquid supply rate of 0.5ml / h, a roller speed of 150 rpm, a slide stroke of 20cm, a spinning voltage of 13kV, and a spinning time of 180min, and the 01-TiO2-PAN electrospinning membrane was obtained after drying.
[0067] Alkaline solution treatment: The 01-TiO2-PAN electrospun membrane was placed in a 1.5 mol / L NaOH solution at 45 °C for 60 min;
[0068] Immersion: Immerse the 01-TiO2-PAN electrospun membrane treated with alkaline solution in 0.01 mol / L AgNO3 solution for 30 min and take it out;
[0069] Heat treatment, cleaning and drying: The impregnated 01-TiO2-PAN electrospinning membrane was placed in an oven at 60°C for reaction for 5 minutes, taken out, cleaned, and dried to obtain product 4.
[0070] Example 5
[0071] Electrospinning: 0.07g TiO2 was evenly dispersed in N,N-dimethylacetamide solution, then 15g polyacrylonitrile was added, stirred at 65℃, and degassed to obtain 13.8wt% TiO2 / PAN spinning solution. Then, the spinning was performed at a liquid supply rate of 0.5ml / h, a roller speed of 150 rpm, a slide stroke of 20cm, a spinning voltage of 13kV, and a spinning time of 180min. After drying, 07-TiO2-PAN electrospinning membrane was obtained.
[0072] Alkaline solution treatment: The 07-TiO2-PAN electrospun membrane was placed in a 0.5 mol / L NaOH solution at 45°C for 60 min;
[0073] Immersion: The 07-TiO2-PAN electrospun membrane treated with alkaline solution was reacted in 0.01 mol / L AgNO3 solution for 30 min and then taken out;
[0074] Heat treatment, cleaning and drying: The impregnated 07-TiO2-PAN electrospinning membrane was placed in an oven at 60°C for reaction for 5 minutes, taken out, cleaned, and dried to obtain product 5.
[0075] The iodine adsorption capacity and total iodine ion removal rate of the composite membrane obtained in the above example are shown in Table 1. The surface morphology and XRD diagram of Example 1 are shown in Figure 1-Figure 2 .
[0076] Table 1 Adsorption capacity of the membrane obtained in the embodiment for iodide ions and the total removal rate of iodide ions after (adsorption-light irradiation)
[0077]
[0078]
[0079] As can be seen from the above, the metal oxide modified polyacrylonitrile electrospun membrane prepared by the present invention has the advantages of simple preparation process and excellent product performance, and the maximum adsorption capacity can reach 90.0 mg / g, which is much higher than the market products. Combined with ultraviolet treatment, the maximum total removal rate of iodine ions in water reaches about 95%. The composite membrane has sufficient raw material sources, relatively low cost, high cost performance, is suitable for treating iodine-containing wastewater, and has good application prospects.
[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A M x O y -PAN composite film, characterized by: Polyacrylonitrile or TiO2-modified polyacrylonitrile is electrospun to obtain polyacrylonitrile or TiO2-modified polyacrylonitrile fiber membrane, which is then treated with an alkali solution, immersed in a metal nitrate solution for reaction, and finally heat-treated to obtain a metal oxide M x O y Modified composite membrane.
2. The M according to claim 1 x O y -PAN composite film, characterized by: The metal oxide is any one of Ag2O or Ag2O-TiO2 binary metal oxide, copper oxide, and cuprous oxide.
3. A kind of M x O y -The preparation method of PAN composite film is characterized by: Step 1: preparing polyacrylonitrile fiber membrane or TiO2 modified polyacrylonitrile fiber membrane; Step 2: treating the obtained polyacrylonitrile fiber membrane or TiO2-modified polyacrylonitrile fiber membrane with an alkaline solution; Step 3: immersing the polyacrylonitrile fiber membrane treated with an alkali solution or the TiO2-modified polyacrylonitrile fiber membrane in a metal nitrate solution for reaction; Step 4: heat-treat the polyacrylonitrile fiber membrane or TiO2-modified polyacrylonitrile fiber membrane treated in step 3, then wash and dry to obtain M x O y -PAN composite film.
4. The M according to claim 3 x O y -The preparation method of PAN composite film is characterized by: The alkaline solution is an alkali metal hydroxide solution with a concentration of 0.5 to 3.0 mol / L.
5. The M according to claim 3 x O y -The preparation method of PAN composite film is characterized by: The metal nitrate solution is AgNO3 solution or Cu(NO3)2 solution.
6. The M according to claim 3 x O y -The preparation method of PAN composite film is characterized by: The heat treatment temperature in step 3 is 50-80° C. and the time is 3-10 minutes.
7. The M according to claim 3 x O y -The preparation method of PAN composite film is characterized by: The preparation process of polyacrylonitrile fiber membrane is as follows: first prepare 13.8wt% polyacrylonitrile spinning solution, then spin at a liquid supply rate of 0.5ml / h, a roller speed of 150 rpm, a slide stroke of 20cm, a spinning voltage of 13kV, and a spinning time of 180min, and obtain PAN fiber membrane after drying.
8. The M according to claim 3 x O y -The preparation method of PAN composite film is characterized by: The preparation process of the TiO2 modified polyacrylonitrile fiber membrane is as follows: a certain amount of TiO2 is uniformly dispersed in an N,N-dimethylacetamide solution, and then PAN :m TiO2 =15:0.01~15:0.07 ratio of polyacrylonitrile, stirring at 65°C, degassing to obtain 13.8wt% TiO2 / PAN spinning solution; then spinning at a liquid supply rate of 0.5ml / h, a roller speed of 150 rpm, a slide stroke of 20cm, a spinning voltage of 13kV, a spinning time of 180min, and drying to obtain TiO2 modified polyacrylonitrile fiber membrane.
9. The M of claim 1 x O y -Application of PAN composite membrane in reducing iodine ion content in water.
10. M obtained by the preparation method according to any one of claims 3 to 8 x O y -Application of PAN composite membrane in reducing iodine ion content in water.